Aggressive behaviour of cherubism in a teenager: 4-years of clinical follow-up associated with radiographic and histological features - Gomes, M. F.; Destro, MFDS; Banzi, ECF; dos Santos, S. H.; Clar, F. A.; Nogueira, T. D. (British Inst Radiology, 2005)
Cherubism is a rare hereditary fibro-osseous childhood disease characterized by bone degradation and fibrous tissue replacement at the angles of the mandible and at the tuberosity areas of the maxilla that leads to prominence of the lower face and an appearance reminiscent of the cherub's portrayal in Renaissance art. This disease has an autosomal dominant hereditary characteristic. The purpose of this report is to analyse laboratory tests, clinicopathological and radiographic features of cherubism and its intraoral manifestations in a patient during 4-years of follow-up, correlating the features observed in this case with those of the literature. Also discussed is the atypical and aggressive behaviour of this case during puberty.
Keywords: cherubism; maxillofacial; jaw complex; intraoral manifestations